The symbolic power of the Evenk language in the context of the stability of the ethnic identity of the Evenks of Yakutia - Danilov, Igor A.; Zakharova, Nataliia E.; Zakharova, Akulina E. (The New Research of Tuva, 2024)
The article analyzes the symbolic power of the Evenki language within the context of the heterogeneous linguistic situation in the Republic of Sakha (Yakutia), Russia. The authors examine the resilience of Evenki ethnic identity as a potential resource for the revitalization of the Evenki language. Based on field research conducted in 2022–2023 in three Evenki settlements in Yakutia (Iengra, Tyanya, and Taymylyr) with varying degrees of language preservation, the study identifies the transformations in the role of the Evenki language within the hierarchy of ethno-defining factors among the local population. It was found that in villages where the Evenki language maintains relatively high vitality, the language remains a key marker of ethnic identity. The study demonstrates that in communities where the language has long been lost, the consolidating role of the Evenki language has shifted towards cultural-traditional and historical-territorial aspects of identity. At the same time, an analysis of language attitudes reveals a solid foundation for the revitalization, preservation, and intergenerational transmission of the Evenki language. The results indicate that despite the heterogeneity of the linguistic situation and varying degrees of language shift, the resilience of the ethnic identity of the Evenki people in Yakutia ensures the high symbolic power of the Evenki language, creating opportunities for its revival. This would require the implementation of a set of locally oriented institutional and sociocultural measures that account for the specific characteristics of each Evenki settlement in the republic and aim to comprehensively support the Evenki language.